2000
DOI: 10.3171/jns.2000.93.6.1078
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral injection of biobond adhesive for removal of cavernous sinus hemangioma

Abstract: The authors present a case in which a cavernous sinus (CS) hemangioma was totally removed following intratumoral injection of a plastic fixation material. This unique method is extremely useful for the removal of CS hemangiomas, which often feature massive intraoperative bleeding as an unsolved problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Treatment of patients with cavernous sinus hemangiomas has generated interest in recent years because the results of surgical intervention are unfavorable, even if new surgical techniques, for example the extradural approach and induced systemic hypotension, are applied [17][18][19][20]. According to some published reports, the lesions are quite radiosensitive; radiosurgery and conventional radiotherapy should therefore be important in overall management [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of patients with cavernous sinus hemangiomas has generated interest in recent years because the results of surgical intervention are unfavorable, even if new surgical techniques, for example the extradural approach and induced systemic hypotension, are applied [17][18][19][20]. According to some published reports, the lesions are quite radiosensitive; radiosurgery and conventional radiotherapy should therefore be important in overall management [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…We divided these 55 cases into two groups on the basis of treatment response shown on the most recent MR images available. Remarkable tumor shrinkage was demonstrated in 39 (70.9%) of 55 patients and the mean radiation dose received was 14 Gy (range [10][11][12][13][14][15][16][17][18][19]. The mean radiation dose received by 16 patients with partial or no change tumor shrinkage was 13.5 Gy (range [10][11][12][13][14][15][16].…”
Section: Dose and Treatment Responsementioning
confidence: 96%
“…65 Several other methods of haemostasis, including intratumoural fibrin glue or plastic adhesive injection, or induced hypotension, have been proposed, but early devascularisation and enbloc removal ensures the most direct means of achieving haemostasis. 63,[66][67][68] In our experience, gamma knife radiosurgery has also been very effective in the primary treatment of cavernous sinus haemangiomas. 69 This finding is supported by several other reports.…”
Section: Cavernous Sinus Haemangiomasmentioning
confidence: 94%
“…11 On the contrary, it is often difficult to remove large or giant tumors totally without performing a debulking procedure by incising the capsule. 7,8,10 For the safe removal of CS cavernous hemangiomas for which embolization is not possible, as shown in this report, some authors have suggested that a superior approach to the cavernous ICA be followed at an early operative stage to interrupt the main feeding source. 11,27 This procedure is not peformed easily until internal de-compression of the lesion has been completed from the lateral approach.…”
Section: Discussionmentioning
confidence: 89%
“…With regard to their diagnosis, the evidence of bone erosion on CT scans, marked hyperintensity on T 2 -weighted MR images, and little to no angiographic blush are characteristic imaging findings. 8,23,30 Two subtypes of cavernous hemangioma of the CS were documented in a pathological report, 27 which revealed marked differences in light microscopic features, difficulty in hemostasis, tumor hardness, and resectability.…”
Section: Discussionmentioning
confidence: 97%